Diurnal Salivary Cortisol in Relation to Body Composition and Heart Rate Variability in Young Adults - Cvijetic, Selma; Keser, Irena; Jurasović, Jasna; Orct, Tatjana; Babić, Željka; Boschiero, Dario; Ilich, Jasminka Z. (Frontiers in Endocrinology, 2022)
Objective: Chronic stress has been related to impaired body composition (bone, muscle, adipose tissue), as well as disturbed autonomic nervous system (ANS), the latter regulated by hypothalamic- pituitary-adrenal (HPA) axis. Our objective was to investigate the relationship between salivary cortisol, body composition and heart rate variability (HRV - highly influenced by ANS), in young student population. Methods: Body composition and HRV parameters were measured using two portable devices based on multi-frequency bioelectrical impedance and photoplethysmography. Body composition included measurement of bone, lean/muscle and adipose tissues. HRV included time domain and frequency domain indices. Salivary cortisol, immediately after awakening, 60 min post awakening and late night was collected and analysed by ELISA. Results: Participants included n=43 healthy university students (39 females, 4 males); 21.1±1.3 years, BMI=21.8±3.4 kg/m2. Skeletal muscle was reduced in most of the participants, bone mass was at the lower normal range, while the fat tissue parameters were normal with only 7% participants being overweight. Cortisol and HRV parameters of sympathetic predominance (low frequency - LF and low frequency/high frequency ratio - LF/HF) were significantly associated with higher fat tissue parameters (fat mass – FM% and intramuscular adipose tissue – IMAT%) (p<0.001 and p=0.035, respectively) and with lower skeletal muscle (p=0.002) and bone mass (p=0.025). Conclusions: The results point to a role of cortisol and ANS in the control of all three body composition compartments, suggesting that the stress can result in adverse effects on body composition, even in young, apparently healthy individuals.